RNA interference analyses suggest a transcript-specific regulatory role for mitochondrial RNA-binding proteins MRP1 and MRP2 in RNA editing and other RNA processing in Trypanosoma brucei - Vondrusková, Eva; van den Burg, Janny; Zíková, Alena; Ernst, Nancy Lewis; Stuart, Kenneth; Benne, Rob; Lukes, Julius (The Journal of biological chemistry, 2005)
Mitochondrial RNA-binding proteins MRP1 and MRP2 occur in a heteromeric complex that appears to play a role in U-insertion/deletion editing in trypanosomes. Reduction in the levels of MRP1 (gBP21) and/or MRP2 (gBP25) mRNA by RNA interference in procyclic Trypanosoma brucei resulted in severe growth inhibition. It also resulted in the loss of both proteins, even when only one of the MRP mRNAs was reduced, indicating a mutual dependence for stability. Elimination of the MRPs gave rise to substantially reduced levels of edited CyB and RPS12 mRNAs but little or no reduction of the level of edited Cox2, Cox3, and A6 mRNAs as measured by poisoned primer extension analyses. In contrast, edited NADH-dehydrogenase (ND) subunit 7 mRNA was increased 5-fold in MRP1+2 double knock-down cells. Furthermore, MRP elimination resulted in reduced levels of Cox1, ND4, and ND5 mRNAs, which are never edited, whereas mitoribosomal 12 S rRNA levels were not affected. These data indicate that MRP1 and MRP2 are not essential for RNA editing per se but, rather, play a regulatory role in the editing of specific transcripts and other RNA processing activities.
Keywords: RNA Interference; vazba proteinů; Blotting, Southern; imunoprecipitace; Cloning, Molecular; DNA primery; RNA protozoální; RNA, Ribosomal; northern blotting; editace RNA; Plasmids; Immunoprecipitation; Southernův blotting; RNA interference; Protein Binding; RNA-Binding Proteins; RNA, Protozoan; messenger RNA; RNA, Messenger; transfekce; RNA; RNA Editing; Blotting, Northern; plazmidy; Protozoan Proteins; klonování DNA; Blotting, Western; western blotting; mitochondriální proteiny; zvířata; Trypanosoma brucei brucei; glycerol; Time Factors; Glycerol; proteiny vázající RNA; Animals; časové faktory; protozoální proteiny; Transfection; RNA ribozomální; Mitochondrial Proteins; DNA Primers